Chemometric analysis of Amaranthus retroflexus in relation to livestock toxicity in southern Australia. (May 2019) - Weston, Paul A.; Gurusinghe, Saliya; Birckhead, Emily; Skoneczny, Dominik; Quinn, Jane C.; Weston, Leslie A.
Abstract: Amaranthus retroflexus L., an introduced invasive weed in southern Australia, has been associated with acute renal failure and/or mortality in a number of livestock species. While its leaves, flowers and stems are generally reported to contain high levels of nitrogen, few studies have fully characterised the chemical composition of A. retroflexus foliage with respect to mammalian toxicity. We performed extensive metabolic profiling of stems, leaves, roots and inflorescence tissues of A. retroflexus collected from three spatially and/or temporally distinct toxicity outbreaks, and report on the 1) composition of primary and secondary metabolites in methanolic extracts of A. retroflexus tissues using HPLC and HPLC-MS QToF and 2) chemometric analysis of A. retroflexus extracts in relation to the associated toxin(s). All tissues of A. retroflexus possessed an abundance of N-containing metabolites, particularly quaternary ammonium compounds which were identified as betaines, two of which (valine betaine and isoleucine betaine) are rarely encountered in plants. Cytotoxicity to murine fibroblasts was highest in extracts of leaf tissue and was associated with a single, a small modified peptide with high similarity to N-acetyl-L-α-aspartyl-L-alanyl-L-α-aspartyl-L-α-glutamyl-O-(carboxymethyl)-L-tyrosyl-L-leucinamide, a synthetic phosphotyrosyl mimic involved in cell signaling processes. One possible mode of action leading to acute renal failure in grazing livestock by a modified peptide such as this is proposed. Graphical abstract: Image 1 Highlights: All tissues of A. retroflexus contained abundant levels of glycine betaine and related compounds. We have identified for the first time valine betaine and isoleucine betaine in A. retroflexus . These are only the second reports of these two uncommon betaines in plants. In vitro toxicity of A. retroflexus was associated with a small, modified peptide.